Praktik Sosial Goenawan Mohamad di Arena Sastra Indonesia pada Tahun 1990-an: Kajian Sosiologi Anthony Giddens - Aprilia Ciptaning Maharani; Dwi Susanto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The purpose of this study is to find out how GM's social practices as agents in the Indonesian literary arena in the 1990s, and the structural responses to these social practices. This research is qualitative. The material object is GM's social practice in the Indonesian literary arena in the 1990s, while the formal object is the arena structure's response to the action. Data analysis was performed by chronological mapping accompanied by decomposition that referred to Anthony Giddens's sociological theories. Based on research that has been done, the results show that GM runs social practices by occupying several arena structures, including Horison, AJ and DKJ, Tempo through Caping, and KUK. The structural response to these actions was manifested in several conflicts, contradictions and acceptances that helped to bolster the existence of GM's literacy in the Indonesian literary arena from the beginning to the 1990s.